Exposing One-Stop Platform Stock Investment Phenomenon: The Role of Generated Content, Fear of Loss, and Financial Literacy - Akmando, Luthfi Jovan Wandy; Adiwijaya, Karto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The one-stop platform of stock investment has a positive effect on technological developments in the world of stock investment. That triggers changes in investor behavior in buying stock. This research investigates the influence of the "stream" feature as User Generated Content (UGC) media as well as the relationship between the Fear of Missing Out (FoMO) phenomenon and investor's financial literacy in buying stocks. This research implements partial least squares-structural equation modeling (PLS-SEM) to conduct quantitative research. Sample data collection was collected using non-probability sampling. This research is limited to Indonesian stock investors, using the Stockbit platform for stock investment, and the research was conducted cross-sectionally. This research found that FoMO effects that investors felt can significantly influence purchasing attitudes, subjective norms, and perceived behavioral control. Meanwhile, the quality of information contained in UGC has a significant positive effect on purchase attitudes and financial literacy can reduce the influence of investor FoMO on purchasing intentions. This research contributes to the extended theory of planned behavior in explaining stock investment behavior and enriches understanding of the influence of UGC, FoMO, and financial literacy on investment decisions. This research also contributes to Stockbit management, psychology practitioners, content creators, and financial consultants in the realm of stocks.